Conditional loss of uterine Pten unfailingly and rapidly induces endometrial cancer in mice - Daikoku, Takiko (2008)
Etiology of endometrial cancer (EMC) is not fully understood. Animal models with rapidly and spontaneously developing EMC will help explore mechanisms of cancer initiation and progression. Pten(+/−) mice are currently being used as a model to study EMC. These females develop atypical endometrial hyperplasia of which ~20% progresses to EMC. In addition, tumors develop in other organs, complicating the use of this model to specifically study EMC. Here we show that conditional deletion of endometrial Pten results in EMC in all female mice as early as one month of age with myometrial invasion occurring by three months. In contrast, conditional deletion of endometrial p53 had no phenotype within this time frame. While mice with endometrial Pten deletion had a lifespan of about five months, mice with combined deletion of endometrial Pten and p53 had a shorter lifespan with an exacerbated disease state. Such rapid development of EMC from homozygous loss of endometrial Pten suggests that this organ is very sensitive to this tumor suppressor gene for tumor development. All lesions at early stages exhibited elevated Cox-2 and phospho-Akt levels, hallmarks of solid tumors. More interestingly, levels of two microRNAs miR-199a(*) and miR-101a that post-transcriptionally inhibit Cox-2 expression, were downregulated in tumors in parallel with Cox-2 upregulation. This mouse model in which the loxP-Cre system has been used to delete endometrial Pten and/or p53 allows us to study in detail the initiation and progression of EMC. These mouse models have the added advantage since they mimic several features of human EMC.